National Politics in Efforts to Equalize Community Rights and Freedom of Expression - Didik Himmawan; Putri Ayu Wulandari (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
This research aims to discuss and analyze the forms of national politics and the public's right to freedom of expression on social media in Indonesia. This research also aims to explain and analyze whether the regulations on national politics and the public's right to freedom of expression are appropriate and in line with the principles of human rights protection. This research uses a normative method. The results show that freedom of expression is both a right and a responsibility in a democratic state. The application of the Electronic Information and Transactions Law (UU ITE) in relation to the fundamental right of every citizen to freedom of opinion and expression cannot be reduced or restricted by anyone, including the state. The state has a responsibility to respect and protect human rights through legislation. Criticism of the government is not a violation of the law because freedom of opinion and expression is guaranteed by the Indonesian constitution. Restrictions on freedom of expression and opinion aim to ensure security and well-being among citizens without violating other human rights.